The Perception of Health Care Professionals and Managers about Resource Allocation in Primary Health Care in Minas Gerais State Municipalities - Santos, Lucas Maia dos; Gonçalves, Márcio Augusto (Organizações & Sociedade, 2021)
This study aimed to examine and describe the perceptions of health professionals and managers about the main phenomena that influence resource allocation in primary health care. Adopting a qualitative approach, the field research was carried out in ten municipalities in Minas Gerais and involved eleven focus groups, six interviews and two semi-structured questionnaires in 2014 and 2015, and nine focus groups and five interviews in 2018, in which participated a total of 133 health professionals and managers. Other sources of evidence were also included, such as non-participating observations, photographs and documents from the Minas Gerais State Health Secretariat and the Ministry of Health. Based on the content analysis, eight categories of phenomena that influence resource allocation in PHC were obtained, derived from daily interactions between the population and health professionals and managers. Our findings show that primary health care is in a process of institutional change, dependent on the validity of actors and institutions, at different institutional levels. Among the determining factors affecting resource allocation in PHC, the main ones are the agency of the actors involved, the health service flow, the private sector, the medical corporatism, the influence of politicians, the municipal management capability, the infrastructure and groups of specific individuals.